Reseñas de libros, por Julio Faúndez Bravo, Eduardo Ortíz, Guillermo Martínez, Víctor Wallis, Marcos Kaplan, Richard Gott, Antonio García, John Gittings - Internacionales, Estudios (Estudios Internacionales, 1968)
-